Fluorescence Characterization of Gold Modified Liposomes with Antisense N-myc DNA Bound to the Magnetisable Particles with Encapsulated Anticancer Drugs (Doxorubicin, Ellipticine and Etoposide) - Skalickova, Sylvie; Nejdl, Lukas; Kudr, Jiri; Ruttkay-Nedecky, Branislav; Jimenez, Ana Maria Jimenez; Kopel, Pavel; Kremplova, Monika; Masarik, Michal; Stiborova, Marie; Eckschlager, Tomas; Adam, Vojtěch; Kizek, Rene (Sensors, 2016)
Liposome-based drug delivery systems hold great potential for cancer therapy. The aim of this study was to design a nanodevice for targeted anchoring of liposomes (with and without cholesterol) with encapsulated anticancer drugs and antisense N-myc gene oligonucleotide attached to its surface. To meet this main aim, liposomes with encapsulated doxorubicin, ellipticine and etoposide were prepared. They were further characterized by measuring their fluorescence intensity, whereas the encapsulation efficiency was estimated to be 16%. The hybridization process of individual oligonucleotides forming the nanoconstruct was investigated spectrophotometrically and electrochemically. The concentrations of ellipticine, doxorubicin and etoposide attached to the nanoconstruct in gold nanoparticle-modified liposomes were found to be 14, 5 and 2 µg·mL(-1), respectively. The study succeeded in demonstrating that liposomes are suitable for the transport of anticancer drugs and the antisense oligonucleotide, which can block the expression of the N-myc gene.
Keywords: liposomy; magnetické nanočástice; elipticiny; Gold; zlato; Magnetite Nanoparticles; Etoposide; lidé; Liposomes; Doxorubicin; protoonkogen n-myc; etoposid; nádory; Neoplasms; antisense DNA; fluorescence; Drug Delivery Systems; Ellipticines; Fluorescence; Humans; lékové transportní systémy; N-Myc Proto-Oncogene Protein; DNA, Antisense; doxorubicin